Manganese Superoxide Dismutase - Mohammedi, Kamel; Bellili-Muñoz, Naïma; Driss, Fathi; Roussel, Ronan; Seta, Nathalie; Fumeron, Frédéric; Hadjadj, Samy; Marre, Michel; Velho, Gilberto (PloS one, 2014)
Oxidative stress is involved in the pathophysiology of diabetic nephropathy. Manganese superoxide dismutase (SOD2) catalyses the dismutation of superoxide, regulates the metabolism of reactive oxygen species in the mitochondria and is highly expressed in the kidney. Plasma concentration of advanced oxidation protein products (AOPP), a marker of oxidative stress, was found to be increased in patients with kidney disease. We investigated associations of SOD2 allelic variations, plasma SOD activity and AOPP concentration with diabetic nephropathy in type 1 diabetic subjects. Eight SNPs in the SOD2 region were analysed in 1285 Caucasian subjects with type 1 diabetes from the SURGENE prospective study (n = 340; 10-year follow-up), GENESIS (n = 501) and GENEDIAB (n = 444) cross-sectional studies. Baseline plasma concentration of AOPP and SOD activity were measured in GENEDIAB participants. Hazard ratio (HR) and odds ratio (OR) were determined for incidence and prevalence of nephropathy. Analyses were adjusted or stratified by retinopathy stages. In the SURGENE cohort, the T-allele of rs4880 (V16A) was associated with the incidence of renal events (new cases, or the progression to a more severe stage of nephropathy; HR 1.99, 95% CI 1.24-3.12, p = 0.004) and with the decline in estimated glomerular filtration rate (eGFR) during follow-up. Similar associations were observed for rs2758329 and rs8031. Associations were replicated in GENESIS/GENEDIAB cohorts, in the subset of participants without proliferative retinopathy, and were confirmed by haplotype analyses. Risk allele and haplotype were also associated with higher plasma AOPP concentration and lower SOD activity. SOD2 allelic variations were associated with the incidence and the progression of diabetic nephropathy, with a faster decline in eGFR and with plasma AOPP concentration and SOD activity in subjects with type 1 diabetes. These results are consistent with a role for SOD2 in the protection against oxidative stress and kidney disease in type 1 diabetes.